From Likes to Self-Likes: Social Support for Teenage Online Social Support and Body Image Among Adolescent TikTok Users in Indonesia - Christania Pingkan Putrinita; Anggie Nur Fitrianti; Kamaratih Purnama Kusuma; Meyta Roida Rebecka Hutapea (Journal of Business, Social and Technology, 2026)
Background: The rapid growth of social media use, particularly TikTok, among adolescents has raised critical concerns about its impact on body image and psychological well-being. Objective: This study aims to analyze the relationship between online social support and body image in adolescent TikTok users in Indonesia. Methods: The study employed a quantitative approach using a survey method with 1,151 vocational school students aged 15–18 years who actively use TikTok. Purposive sampling was utilized to select participants. The instruments included the Multidimensional Body Self Relations Questionnaire-Appearance Scale (MBSRQ-AS) and a social support scale designed for social networks. Results: Data analysis was conducted using Pearson correlation, t-test, and ANOVA. The results revealed a significant positive relationship between online social support and body image (r = 0.460; p < 0.01). Additionally, significant differences in body image were observed based on gender, the presence of influencers as role models, duration of TikTok use, and primary sources of social support. Online social support demonstrated a contribution to enhancing adolescent body image, although other external factors also play a role. Conclusion: These findings contribute to digital communication studies and provide evidence-based guidance for parents, educators, and policymakers to foster digital literacy and cultivate a body-positive online environment for adolescents.